PO-19 - Platelet (PLT) adhesion under flow condition in essential thrombocythemia (ET) and polycythemia vera (PV) is variably influenced according to patient mutational status. Issue 140 (April 2016) - Vignoli, A.; Tessarolo, S.; Marchetti, M.; Gamba, S.; Piras, F.; Finazzi, G.; van der Meijden, P.E.J.; Swieringa, F.; ten Cate, H.; Heemskerk, J.W.M.; Rambaldi, A.; Falanga, A.
Abstract : Introduction: The myeloproliferative neoplasms ET and PV are characterized by a high incidence of both arterial and venous thrombosis, and/or microcirculatory disturbances. Three somatic mutations, i.e. JAK2-V617F, Calreticulin (CalR) and MPL, commonly found in these diseases, correlate with different thrombotic risk levels. Aim: To analyze the influence of JAK2-V617F, CalR and MPL mutations on PLT adhesion, evaluated by a dynamic method under flow conditions in a group of patients with ET and PV. Materials and Methods: 86 patients, i.e. 51 ET (19 M/32 F; age range 32-86 years) and 35 PV (22 M/13 F; 41-83 yrs.), and 24 healthy controls (13 M/11 F; 28-61 yrs.) were enrolled upon informed consent. For the adhesion assay, peripheral venous whole blood was perfused over collagen for 4' at a 1, 000 s-1 shear rate. PLTs were then stained with an anti-P-selectin-FITC antibody to evaluate PLT activation, and annexin V-AlexaFluor647 to detect procoagulant phosphatidylserine expression. Then, images of adherent PLTs in random fields were taken using phase contrast and fluorescence imaging by EVOS® fluorescence microscope. Results are mean ± SEM of the % area covered by PLTs, or as the % of adherent PLTs positive for P-selectin or phosphatidylserine. Main hematological parameters and mutational status were recorded. Results: PLT adhesion was significantly (p < 0.01) greater in ET (44.6 ± 1.6%) and PV patients (49.0 ± 1.9%) compared to controls (37.9 ± 1.7%). In ET, PLT adhesion was highest in JAK2-V617F mutation carriers (n = 23), followed by CalR-positive (n = 16) and triple negative subjects (n = 9), and lowest in the MPL-positive patients (n = 3). In PV, no difference in PLT adhesion was observed between JAK2-V617F heterozygous and homozygous subjects. P-selectin expression by adherent PLTs was not statistically different between patients and controls. Differently, phosphatidylserine expression on adherent PLTs was significantly reduced (p < 0.01) in both ET and PV compared to healthy subjects. In ET patients, a significant (p < 0.05) correlation was found between PLT adhesion and PLT count in JAK2-V617F and CalR-positive mutation carriers. Multivariate regression analysis adjusted for age and sex, confirmed PLT count as a significant determinant of PLT adhesion in JAK2-V617F positive patients only. Conclusions: ET and PV platelets show an increased adhesion to collagen in vitro, particularly in those carrying the JAK2-V617F mutation. A prospective study is ongoing to evaluate the predictive value of our PLT thrombus formation dynamic model for the thrombotic risk in ET and PV patients. Acknowledgement: Project funded by "AIRC-IG2013" grant Nr. 14505 from the "Italian Association for Cancer Research" (A.I.R.C.).